Training Malaysian pharmacy undergraduates with knowledge and skills on smoking cessation - Simansalam , Saraswathi; Brewster, Joan M.; Nik Mohamed, Mohamad Haniki (American Association of Colleges of Pharmacy (AACP), 2015)
To evaluate the feasibility of an online training module, Certified Smoking Cessation Service Provider (CSCSP), developed for practicing pharmacists to equip pharmacy students with knowledge necessary for smoking cessation counseling and to assess the changes in student knowledge and skills regarding smoking cessation following training. Sixty third-year and 80 fourth-year pharmacy undergraduates (N5140) were given access to an online module, the main intervention in the study. Two linkable questionnaires were administered to assess students’ preintervention and postintervention knowledge. For the third-year students, an addi- tional role-play training component was incorporated, and student skills were assessed during week 14 with an Objective Structured Clinical Examination (OSCE). Preintervention and postintervention knowledge assessments were completed by 130 (92.8%) students. Sixty-six students scored above 50% for the knowledge component postintervention, compared to 13 at preintervention, demonstrating significant improvement (x2(1, N5130)532, p50.003). All third-year students completed the intervention, and 66.7% were able to counsel excel- lently for smoking cessation, scoring more than 80%. The CSCSP online module developed for practicing professionals was found suitable for equipping pharmacy undergraduates with knowledge on smoking cessation topics. The module, along with role-play training, also equipped students with knowledge and skills to provide smoking cessation counseling.